2004
DOI: 10.1128/aem.70.5.2989-3004.2004
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Dormancy of Mycobacterium avium subsp. paratuberculosis in theEnvironment

Abstract: The survival of Mycobacterium avium subsp. paratuberculosis was studied by culture of fecal material sampled at intervals for up to 117 weeks from soil and grass in pasture plots and boxes. Survival for up to 55 weeks was observed in a dry fully shaded environment, with much shorter survival times in unshaded locations. Moisture and application of lime to soil did not affect survival. UV radiation was an unlikely factor, but infrared wavelengths leading to diurnal temperature flux may be the significant detrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
244
2
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 279 publications
(260 citation statements)
references
References 41 publications
4
244
2
6
Order By: Relevance
“…The difference in herd density is striking: at GIWA it is approximately 0.04 elk per hectare (140 elk on 3,450 ha), while herd density at PRNS is at least 0.38 elk per hectare (.400 elk on 1,040 ha; Manning et al, 2003). In addition to a higher herd density, continued herd infection with clinically affected animals and the subsequent increased environmental fecal contamination as well as specific environmental factors at PRNS, such as lower mean daily temperature (11.4 C vs. 16.1 C), higher annual mean precipitation (95.2 cm vs. 48.9 cm), and acidic soil (pH56.0 at PRNS), may facilitate survival of MAP in the environment (Gogan et al, 1989;Manning and Collins, 2001;Hoar, 2002;Whittington et al, 2004). Furthermore, elk at PRNS, unlike elk at GIWA, have shown clinical and biological evidence of copper deficiency, associated with decreased immunocompetency in ruminants, which may predispose the PRNS herd to clinical paratuberculosis (Gogan et al, 1989;Stabel and Spears, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The difference in herd density is striking: at GIWA it is approximately 0.04 elk per hectare (140 elk on 3,450 ha), while herd density at PRNS is at least 0.38 elk per hectare (.400 elk on 1,040 ha; Manning et al, 2003). In addition to a higher herd density, continued herd infection with clinically affected animals and the subsequent increased environmental fecal contamination as well as specific environmental factors at PRNS, such as lower mean daily temperature (11.4 C vs. 16.1 C), higher annual mean precipitation (95.2 cm vs. 48.9 cm), and acidic soil (pH56.0 at PRNS), may facilitate survival of MAP in the environment (Gogan et al, 1989;Manning and Collins, 2001;Hoar, 2002;Whittington et al, 2004). Furthermore, elk at PRNS, unlike elk at GIWA, have shown clinical and biological evidence of copper deficiency, associated with decreased immunocompetency in ruminants, which may predispose the PRNS herd to clinical paratuberculosis (Gogan et al, 1989;Stabel and Spears, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in a study conducted in the Netherlands, soil pH was not significantly different between seropositive and seronegative dairy cattle herds (Muskens et al, 2003). Moreover, the application of lime to the soil (to increase pH) appeared not to affect the survival of MAP in an Australian field trial (Whittington et al, 2004). Apart from soil iron content and pH, soil type was also reported to affect the survival of MAP, and hence the distribution of JD by some (Reviriego et al, 2000;Ward and Perez, 2004) but not by others (Turnquist et al, 1991).…”
Section: Introductionmentioning
confidence: 69%
“…Organic carbon, an indicator of soil organic matter content (Baldock and Skjemstad, 1999) might favour the survival of MAP, either directly by providing essential nutrients for its continued existence outside the biological host or indirectly by increasing pasture growth and thus shading which is reported to be favourable for MAP survival (Whittington et al, 2004). Organic matter also increases the water holding capacity of soil (Krull et al, 2004) but soil moisture has not yet been demonstrated to influence survival of MAP (Whittington et al, 2004). Regardless of the uncertainty about moisture, MAP would be available in greater numbers to the animals grazing on soils with a higher organic matter content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high lipid content and heavy cross-linking of these layers in the cell wall is thought to enable mycobacteria to resist antibiotics, UV exposure, heat treatment, and other environmental insults. [7][8][9][10] Proteins containing the NlpC/P60 superfamily domain (pfam00877) are important in bacterial physiology 11 and virulence. 12,13 A Mycobacterium tuberculosis gene, Rv2190c, encodes an NlpC/P60 protein that is required for virulence in the mouse model of TB and was shown to be immunogenic in the context of infection.…”
Section: Introductionmentioning
confidence: 99%